Agenda Setting of News Coverage on the Death of an Online Motorcycle Taxi Driver Caused by a Brimob Tactical Vehicle in Kompas.com and Liputan6.com Digital Media - Khairani , Najmi Rizki; Himmah, Rif’atul (Yayasan Meira Visi Persada, 2025)
This study aims to examine how two mainstream digital media outlets, Kompas.com and Liputan6.com, constructed the news agenda surrounding the death of an online motorcycle taxi (ojol) driver who was run over by a Brimob tactical vehicle during a demonstration riot in Jakarta in August 2025. The study employs the agenda-setting theory, using a qualitative approach and the content analysis method. Data were collected from online news articles published by both media outlets between August 28–31, 2025, that explicitly discussed the tragedy. The findings show that Kompas.com emphasized aspects of institutional responsibility and law enforcement accountability, while Liputan6.com focused more on humanitarian dimensions and social solidarity. These differences indicate that the process of media agenda formation is not neutral but is influenced by editorial orientation and audience characteristics. The study highlights the strategic role of the media in directing public attention toward issues of humanity and police violence in Indonesia